2012
DOI: 10.1063/1.4767679
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction photodiode fabricated from hydrogen treated ZnO nanowires grown on p-silicon substrate

Abstract: A heterojunction photodiode was fabricated from ZnO nanowires (NWs) grown on a p-type Si (100) substrate using a hydrothermal method. Post growth hydrogen treatment was used to improve the conductivity of the ZnO NWs. The heterojunction photodiode showed diode characteristics with low reverse saturation current (5.58 Â 10 À7 A), relatively fast transient response, and high responsivity (22 A/W at 363 nm). Experiments show that the photoresponsivity of the photodiode is dependent on the polarity of the voltages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…However, they [14] observed a very poor forwardto-reverse current ratio (~2 at ±4 V) with a very large reverse saturation current (~4.6×10 -5 A). After critical review of the above works, it is observed that, in general, the n-ZnO thin film grown on a suitable seed layercovered p-Si substrate can help to improve the performance of n-ZnO thin film/p-Si heterojunction photodetectors [9][10][11]. Since the growth of a seed layer is an additional step required in the fabrication process, the cost of fabrication is higher than that of the devices without seed layer.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, they [14] observed a very poor forwardto-reverse current ratio (~2 at ±4 V) with a very large reverse saturation current (~4.6×10 -5 A). After critical review of the above works, it is observed that, in general, the n-ZnO thin film grown on a suitable seed layercovered p-Si substrate can help to improve the performance of n-ZnO thin film/p-Si heterojunction photodetectors [9][10][11]. Since the growth of a seed layer is an additional step required in the fabrication process, the cost of fabrication is higher than that of the devices without seed layer.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, many researchers are trying to explore the low-cost, environment friendly and wide band gap (~3.34 eV) zinc oxide (ZnO) material with large exciton energy (~60 meV larger than GaN ~25 meV) for the UV detection applications [5,6]. They have shown their interest to investigate ZnO based UV photodetectors with different configurations such as Schottky diode [5,6], MSM (metal-semiconductor-metal) [3,7,8], MISM (metalinsulator-semiconductor-metal) [2,8] and p-n heterojunction [9][10][11][12][13] photodiode structures. Since, ZnO is an intrinsically n-type semiconductor, the fabrication of a stable and controllable p-type ZnO thin film is very difficult [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterojunctions are widely used in optoelectronic devices such as light-emitting diodes (LEDs) [1][2][3][4], laser diodes [5,6], and photodiodes (PDs) [7][8][9] because they enable manipulating either hole or electron transport selectively by applying an appropriate band alignment. The specific band alignment can either increase carrier recombination in a LED or move photocarriers into appropriate contact in a PD.…”
Section: Introductionmentioning
confidence: 99%